PELAKSANAAN PEMBANGUNAN BERTERASKAN ISLAM: KAJIAN KES KOMUNITI ISLAM BAN NUA, HATYAI, THAILAND - Hanapi, Dr. Mohd Shukri (Journal of Techno-Social, 2014)
The Ban Nua Muslim community is a Muslim community that is smack in themiddle of the non-Muslim community (Buddhist) in Hatyai, Thailand. Althoughthey are a small community and are is such a predicament, they are still able toimplement Islamic-based development (IbD). In other words, they are able todevelop an Islamic community complete with numerous infrastructures such as amosque, not only as a place for prayer but it has a clinic, a library, a conferencehall, a cooperative and a Zakat Centre (Baitul Zakat). Besides that, this Islamiccommunity has a school that adheres to the Islamic education system. They notonly have worked hard to develop the physical aspects but also the spiritualaspects. The physical aspects were developed through general religious servitudesuch as employment, seeking knowledge, stimulating the community’s economy, business and homestay services, while the spiritual aspects were developed through specific religious servitudes such as prayers, fasting, running the Zakat Centre, reciting the al-Qur’an, devotional recitations (zikr) and giving alms (sadaqah). The question is what tasawwur (worldview) was used to design their development? and how was the tasawwur formed? To answer both thesequestions, this article has two objectives. First, to identify the tasawwur that has designed the development of the Ban Nua Islamic community; and second, to analyse the developmental worldview of the Ban Nua Islamic community. Thefindings from the qualitative research had found that the development of the Ban Nua Islamic community in Hatyai, Thailand was designed according to altasawwur al-Islamiy (Islamic worldview). It has three main elements such asibadah (religious servitude), imarah (general or social leadership) and khalifah(religious leadership). Based on this tasawwur the development of the Ban NuaIslamic community in Hatyai, Thailand was implemented.